2021
DOI: 10.1002/hed.26840
|View full text |Cite
|
Sign up to set email alerts
|

Role of primary tumor resection in patients with metastatic medullary thyroid cancer who have unresectable distant metastases

Abstract: Background Whether patients with medullary thyroid carcinoma (MTC) who have unresectable synchronous distant metastases should undergo primary surgical resection (PTR) remains controversial. This study aimed to identify predictive factors associated with the survival of such patients. Methods We conducted a retrospective study of patients with MTC who were registered in the Surveillance, Epidemiology, and End Results registry. The overall and cancer‐specific mortality rates were assessed using risk‐adjusted Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Результати останніх спостережень свідчать, що серед хворих із віддаленими метастазами МК, яким проведена тиреоїдектомія та лімфодисекція, відмічена менша смертність та вищі показники терміну виживання порівняно з хворими, яким операція на ЩЗ проведена не була. Отже, таку стандартну хірургічну тактику вважають доцільною і для пацієнтів із віддаленими метастазами МК ЩЗ [38].…”
Section: хірургічне лікуванняunclassified
“…Результати останніх спостережень свідчать, що серед хворих із віддаленими метастазами МК, яким проведена тиреоїдектомія та лімфодисекція, відмічена менша смертність та вищі показники терміну виживання порівняно з хворими, яким операція на ЩЗ проведена не була. Отже, таку стандартну хірургічну тактику вважають доцільною і для пацієнтів із віддаленими метастазами МК ЩЗ [38].…”
Section: хірургічне лікуванняunclassified
“…Primary tumor resection in patients with unresectable distant metastases also remains controversial [ 75 ]. In this case, the 2015 Revised ATA Guidelines recommended less aggressive surgery in the central and lateral lymph node compartments to avoid adverse side effects [ 25 ].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In this case, the 2015 Revised ATA Guidelines recommended less aggressive surgery in the central and lateral lymph node compartments to avoid adverse side effects [ 25 ]. However, Zhuang et al [ 75 ] in their paper found that primary tumor resection in these patients not only has a palliative role but also prolongs their median overall survival, unlike most palliative surgeries. Unfortunately, they did not specify exactly which lymph node compartments were resected in his patients [ 75 ].…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation